Design of 4-digit Count-Up with 7-Segment 5-Inch SM415001L - Sulistyanto, Muhammad Prayadi (Journal of Robotics and Control (JRC), 2020)
In daily life we have encountered many 7-segment uses. 7-segment commonly used to display public information or can also display the number of calculations (counters). Control Decoder as a 7-segment driver has also been widely marketed, which is commonly found are IC CMOS and TTL as the decoder controller. Various methods are used to counter the final goal, which is to find out the number of objects. In this research, researchers tried to do a 4-digit count-up by using the CD4510B CMOS IC as a BCD Count-Up and CD4511B as a 5-inch BCD to 7-segment decoder SM415001L and from the results of this research, the use of CD4510B ICs as BCD Up / Down Counter can generate binary numbers according to the results of the counter that is on pins Q1, Q2, Q3, and Q4. IC CMOS CD4511B which according to the datasheet is intended for 7-segment common cathode, can also be used for 7-segment common anode drivers by adding logic inverting circuits using transistors BC547 and CD4511B CMOS IC combined with a logic inverting circuit, the 7-segment 5 Inch SM415001L can display Count-Up numbers from 0000 to 9999